(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
CITAC (Coimbra’s Academy Theatrical Initiation Circle) is a university theater group created in 1956 in Coimbra, Portugal. The history of this group was used as a case study, leading us to the idea that there are theoretical conditions for the dramatic play to be an activator in the production of the artistic avant-garde and, endorsed in its mechanisms, is the ability to reinvent social resistance.